2010
DOI: 10.1103/physrevb.81.165416
|View full text |Cite
|
Sign up to set email alerts
|

Formation of carbon nanotubes:In situoptical analysis using laser-induced incandescence and laser-induced fluorescence

Abstract: Gas-phase production of carbon nanotubes in presence of a metal catalyst with a continuous wave CO 2 laser is investigated by combining coherent anti-Stokes Raman scattering ͑CARS͒, laser-induced fluorescence ͑LIF͒, and laser-induced incandescence ͑LII͒. These in situ techniques provide a unique investigation of the different transformation processes of the primarily carbon and metal vapors issued from the vaporization of the target by the laser and the temperature at which these processes occur. Continuous-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…For example, with the use of CW lasers in this process for the ablation of carbonaceous material from a solid target, the resulting thermal radiation in the plume is analyzed for particle temperature [488,489]. Cau et al [490] reported on the measurement of soot-particle sizes via time-resolved pulsed LII in such a process.…”
Section: Engineered Nanoparticlesmentioning
confidence: 99%
“…For example, with the use of CW lasers in this process for the ablation of carbonaceous material from a solid target, the resulting thermal radiation in the plume is analyzed for particle temperature [488,489]. Cau et al [490] reported on the measurement of soot-particle sizes via time-resolved pulsed LII in such a process.…”
Section: Engineered Nanoparticlesmentioning
confidence: 99%
“…Nevertheless, TiRe-LII shows promise for interrogating this morphology, since signal decay rate is roughly proportional to the heat transfer surface area. Cau et al [ 177 ] interpreted TiRe-LII signals from soot and CNTs using a model developed by Krüger et al [ 191 ] for soot, but without accounting for the morphological differences between these two material types. Mitrani and Shneider [ 179 ] presented a simple heat transfer model for MWCNTs, which accounted for their cylindrical shape and allowed for non-uniform temperatures within the nanomaterial.…”
Section: Non-soot Carbonaceous Materialsmentioning
confidence: 99%
“…The principles of Laser Induced Fluorescence as applied to C2 detection in low temperature plasmas are described in refs. [26][27][28]. Because signal detection is at a different wavelength from the laser wavelength, PLIF is insensitive to scattered laser light, which can be significant in the arc environment.…”
Section: Planar Laser Induced Fluorescencementioning
confidence: 99%